Decision Support Framework for Selection of 3PL Service Providers: Dominance-Based Approach in Combination with Grey Set Theory - Sen, Dilip Kumar; Datta, Saurav; Mahapatra, Siba Sankar (International journal of information technology & decision making, 2017)
Since past two decades, logistics outsourcing has got immense importance in the context of supply chain management. Logistics outsourcing or outsourcing of third party logistics (3PL) comprises involvement of outside firms to execute logistics activities of a firm efficiently. As deployment of 3PL providers has gained huge momentum in recent times, appropriate selection of 3PL providers seems indeed a necessity. The present work intends to propose a decision support framework for evaluation and selection of 3PL providers in pursuit of fulfilling various business needs. A decision support framework based on dominance measure concept integrated with grey set theory has been projected herein. Result obtained thereof has been compared to that of grey-TOPSIS. A case empirical research has also been reported. The proposed dominance-based decision support system in light of grey set theory has been conceptualized and is basically a simplified version of TODIM and PROMETHEE. It explores dominance between two alternatives with respect to a particular criterion, based on which a global dominance measure is computed to facilitate deriving ranking order of candidate 3PL providers. The proposed approach delineated in this research seems straightforward, easy to execute and can exclude complex and tedious computational steps of TODIM as well as PROMETHEE.